Peach palm, Bactris gasipaes Kunth - Mora-Urpí, J.; Weber, John C.; Clement, C.R. (1997)
Yielding fruits and palm hearts, peach palm (Bactris gasipaes) was a staple food crop for many pre-Columbian Amerindian communities in the lowland humid neotropics. The gene pool of cultivated peach palm and its wild relatives is rich in diversity but is subject to genetic erosion creating an urgent need to sample and conserve germplasm. This booklet provides an overview of existing knowledge of the genus with emphasis on genetic resources. Chapters cover the following topics: taxonomy and distribution, botanical description, uses and properties, origin and domestication, genetic diversity, collecting and evaluation, breeding, propagation, agronomy, production areas, commercial potential, limitations and future prospects. An appendix presents details of institutions and scientists managing gene banks and conduction research on peach palm. (Abstract © CAB ABSTRACTS, CAB International)